Local NO2 concentrations and asthma among over-50s in Ireland: A microdata analysis. (31st May 2020) - Carthy, Philip; Ó Domhnaill, Aonghus; O'Mahony, Margaret; Nolan, Anne; Moriarty, Frank; Broderick, Brian; Hennessy, Martina; Donnelly, Aoife; Naughton, Owen; Lyons, Sean
Abstract: Background: Links between air pollution and asthma are less well established for older adults than some younger groups. Nitrogen dioxide (NO2 ) concentrations are widely used as an indicator of transport-related air pollution, and some literature suggests NO2 may directly affect asthma. Methods: This study used data on 8162 adults >50 years old in the Republic of Ireland to model associations between estimated annual outdoor concentration of NO2 and the probability of having asthma. Individual-level geo-coded survey data from The Irish Longitudinal Study on Ageing (TILDA) were linked to model-based estimates of annual average NO2 at 50 m resolution. Asthma was identified using two methods: self-reported diagnoses and respondents' use of medications related to obstructive airway diseases. Logistic regressions were used to model the relationships. Results: NO2 concentrations were positively associated with the probability of asthma [marginal effect (ME) per 1 ppb of airborne NO2 = 0.24 percentage points asthma self-report, 95% confidence interval (CI) 0.06–0.42, mean asthma prevalence 0.09; for use of relevant medications ME = 0.21 percentage points, 95% CI 0.049–0.37, mean prevalence 0.069]. Results were robust to varying model specification and time period. Respondents in the top fifth percentile of NO2 exposure had a larger effect size but also greater standard error (ME = 2.4 percentage points asthma self-report, 95% CI −0. 49 to 5.3). Conclusions: Associations between local air pollution and asthma among older adults were found at relatively low concentrations. To illustrate this, the marginal effect of an increase in annual average NO2 concentration from sample minimum to median (2.5 ppb) represented about 7–8% of the sample average prevalence of asthma.